MANEJO DO EXCESSO DE PESO EM MULHERES NA ATENÇÃO PRIMÁRIA - Aline Cristine Souza Lopes; Raquel De Deus Mendonça; Mariana Carvalho Menezes; Paula Martins Horta; Luana Caroline dos Santos (Universidade do Estado do Rio de Janeiro, 2018)
Objective: To compare two strategies for weight loss conducted with overweight women guided by the regular practice of physical exercises and nutritional education in Primary Health Care services. Methods: A non-randomized and controlled intervention study was conducted for 10 months with overweight women over 20 years old. The control group included women who participated in the collective nutritional intervention in addition to practicing regular physical exercises, and the intervention group included women who participated in these activities in addition to individual nutritional counseling. Results: Fifty-two women were evaluated (intervention group: 26; control group: 26) at the age of 50 years and mean body mass index of 30kg/m2. After the nutritional intervention, weight (p=0.002), body mass index (p=0.002) and waist circumference (p=0.005) reductions were observed in the intervention group. There were no significant changes in the control group. Conclusion: Associating nutritional individual counseling to collective nutritional intervention and to the practice of physical exercise enabled improvement in the anthropometric profile of women, thus reinforcing the importance of integrating actions from health services for effective overweight management. DOI: 10.12957/demetra.2018.36566